The Student Care and Support System of School Administrators in the Krung Thonburi Group Under Bangkok Primary Educational Service Area Office - Sakunkamjornkit, Panitchapong; Sakunkamjornkit, Panitchapong (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: 1) study the administration of the student care and support system of school administrators in Krung Thonburi Group under Bangkok Primary Educational Service Area Office; and 2) to compare the teacher opinions on the administration of the student care and support system of school administrators in Krung Thonburi Group under Bangkok Primary Educational Service Area Office, classified by gender, age, education level and work experience. The study samples consisted of 262 teachers selected throungh stratified random sampling according to school size. The research instrument were questionnaires with content validity, IOC values 1.00 all items, a reliability value of .98. The data analysis utilityed frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and LSD. The research findings revealed that: 1) the administration of the student care and support system of school administrators in Krung Thonburi Group under Bangkok Primary Educational Service Area Office was at the highest level in overall and particular aspects, ranking from the highest to the lowest mean; student recognition individually, Student promotion, student screening, prevention and resolution of problems and student transferring, respectively. 2) with the regard to teachers' opinions on the administration of the student care and support system of school administrators in Krung Thonburi Group under Bangkok Primary Educational Service Area Office, gender and educational level showed no differentes in overall and particular aspect, while the age and work experience found statistically significant differences at the level of .01 and .05 in overall.